KEDUDUKAN PENGADILAN ADAT DALAM RANGKA MENYELESAIKAN SENGKETA TANAH - Jushendri Jushendri (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2019)
The land is very important for human life, this can be seen from the many land disputes that have long been a social reality in every society even though they have different forms and identities. This study uses a normative juridical approach to data analysis using an interactive model. The results showed that disputes that occur in the community vary between overlapping, Quality of Human Resources of the Apparatus Implementing the Regulation of Agrarian Resources, Settlement of disputes in the community can be broadly classified into two kinds of ways, namely through the courts (litigation) and in outside the court (non litigation). Settlement of disputes outside the court that is often carried out by the community includes involving two or more interested parties (negotiations), a dispute resolution process in which the disputing parties utilize the assistance of an independent third party as a mediator (mediator) and involve more than two parties whose task is to assist parties who litigate by finding a way out together (facilitation).